THE CONTENT OF THE METHODOLOGY FOR ASSESSING THE ENVIRONMENTAL AND ECONOMIC EFFICIENCY OF INDUSTRIAL ENTERPRISES (World Economics and Finance Bulletin, 2024)
This article discusses the essence and significance of using a methodology for assessing the ecological and economic efficiency of industrial enterprises. Additionally, it presents formulas for evaluating the effectiveness of environmental protection measures and all types of prevented damages. The methodology for assessing ecological and economic efficiency is based on the principles of economically justifying environmental protection activities. Furthermore, the positive outcomes of applying this methodology in industrial enterprises are summarized.